Digital Marketing Transformation in Hajj and Umrah Agencies: A Systematic Literature Review - Anisa Ul Husna; M. Azizzullah Ilyas; Sari Rahma Nurfadilah; Berkat Rizky; Okta Agustiawan (Indonesian Journal of Da'wah Management Scholars, 2025)
Purpose – This study analyzes the evolution of digital marketing strategies used by Hajj and Umrah travel agencies in Indonesia from 2021 to 2025. Design/methodology/approach – A Systematic Literature Review (SLR) approach was used to collect data, analyze, assess, and conclude articles. Data analysis took place between 2021 and 2025. Findings – From 850 articles identified, 118 were selected for analysis. The findings show a major shift from traditional marketing approaches toward fully integrated digital strategies. By 2023–2025, digital marketing became the primary tool for competition, with agencies relying on websites, SEO, social media, paid ads, WhatsApp Business, and content-based engagement to build trust and attract pilgrims. Research implications – The study concludes that digital marketing is now essential for maintaining competitiveness in the Hajj and Umrah industry and highlights the need for personalized digital experiences and continuous adaptation to consumer behavior. Originality/value – Previous research has focused on the interplay of digital marketing, but few studies have focused on the transformation of digital marketing in Umrah travel agencies.